THE UTILIZATION OF RECYCLED CONCRETE AGGREGATE FROM CONSTRUCTION WASTE AS VERTICAL FILTER - Adnan, Suraya Hani; Abd Roni, Norwardatun; Hamidon, Nuramidah (ASSOCIATION OF INDIAN PHARMACIST-AIP, 2020)
The eutrophication in surface water is one of the problem cause by the higher amount of phosphorus (P). Nevertheless, the existing conventional wastewater treatment system to remove phosphorus is require a complex process. Hence, a system using environmental friendly should be adept to overcome this problem. Recycled concrete aggregate (RCA) used as a filter system issue as an alternative technology for phosphorus removal. This can overcome the problem of construction site waste by converting the waste into something valuable products. Thus, this study aim to investigate the physical and chemical characteristic of RCA that influenced adsorption of P and to determine the percentage of P removal by using two different size of RCA which is (5 mm to 10 mm) and (25 mm to 30 mm). A total of five vertical recycled concrete aggregate filter laboratory scale was design using recycled concrete aggregate and five different concentration of synthetic wastewater which is 10 – 50 mg/L was prepared. Samples were taken from the influent and effluent filters to be tested once a week, and analyzed to determine the amount of pH, the uptake capacity of Phosphorus (q) and the percentage of Phosphorus removal (%).RCA was analyzed using Scanning Electron Microscopy (SEM) and Energy-dispersive X-ray spectroscopy(EDX) testing to determine chemical composition. Results shows that RCA is highly contained with Aluminium, Calcium and Magnesium elements that enhanced the Phosphorus adsorption. The RCA with size 5 mm to 10 mm and synthetic wastewater 10 mg/L display high potential in removing P with 99.54% removal at pH 9.77. Furthermore, this RCA also shows the highest uptake capacity (q) of 3.45 at concentration of synthetic wastewater 50 mg/L. The lower concentration of synthetic wastewater, smaller size of RCA and higher pH have slightly better Phosphorus removal efficiency. In conclusion. RCA has a potential in removing P from synthetic wastewater.